aplikasi perpustakaan berbasis web menggunakan metode RUP (Rational Unified Process) (study kasus SMK Miftahussalam) - Riyanto, Ade; Supriatman, Rian Dwicahya; Sidiq, Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Several errors in the data collection were caused by the manual data entry and bookkeeping that was mostly done by hand. To resolve this issue, work is being done on developing a web application using PHP with the Laravel Framework and a MySQL database. The development methodology that is employed is the Rational Unified Process (RUP), which consists of an Inception phase, an Elaboration phase, an Implementation phase, and a Transition phase that involves Blackbox Testing. This application focuses on automating the book signing and editing processes.